John Calvin and postmodern spirituality - P.H. Fick (In die Skriflig, 2010)
Postmodernists reject universal truth claims and brand them as violent impositions on a person by powerful institutions. Postmodernist spirituality seeks for a more subjective, life- experience based attitude towards values and truths of the Bible and relationship in community. Careful consideration should be given to the issues of community, knowledge/truth, faith, and faith experience. This article will show that, in his “Institutes”, Calvin gives ample attention to faith, the liberating truth about God as revealed in Jesus Christ, and to the Chris- tian’s intimate relationship with Him. Being in Christ, commu- nion with Christ or the “unio mystica cum Christo” through faith as a central theme in Calvin’s theology, needs to be redis- covered and re-applied to reformed spirituality as apologetic means in a postmodern world. This treasure should satisfy the kind of spirituality postmodernists yearn for.